2015
DOI: 10.1063/1.4906540
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of neutral and charged species of one- and two-dimensional models of graphene nanoribbons using multireference theory

Abstract: This study examines the dependence of the polyradical character of charged quasi-linear n-acenes and two-dimensional periacenes used as models for graphene nanoribbons in comparison to the corresponding neutral compounds. For this purpose, high-level ab initio calculations have been performed using the multireference averaged quadratic coupled cluster theory. Vertical ionization energies and electron affinities have been computed. Systematic tests show that the dependence on chain length of these quantities ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…We further analyzed the multi-configurational character of the electronic ground state of several polyacenes in Table I. In contrast to the series of alkane molecules, we observe a progressively strong multi-configurational character in agreement with previous studies [56][57][58][59][60][61][62][63][64] . However, we see a saturation because our diagnostic condenses information from all orbitals into one number while previous studies report natural orbital occupation numbers (NOONs) of all π-orbitals.…”
Section: B Size Independencesupporting
confidence: 87%
“…We further analyzed the multi-configurational character of the electronic ground state of several polyacenes in Table I. In contrast to the series of alkane molecules, we observe a progressively strong multi-configurational character in agreement with previous studies [56][57][58][59][60][61][62][63][64] . However, we see a saturation because our diagnostic condenses information from all orbitals into one number while previous studies report natural orbital occupation numbers (NOONs) of all π-orbitals.…”
Section: B Size Independencesupporting
confidence: 87%
“…These methods will be designated as p-MR-CISD and p-MR-AQCC. It has been shown previously in calculations on oligoacenes and periacenes [39,42] that the polyradical character of these systems and the singlet-triplet gap can be well described in this way. First, CASSCF calculations were performed with CAS(10,10), except for system 1 for which CAS(6,6) was used.…”
Section: Computational Detailsmentioning
confidence: 82%
“…In particular, the MR‐AQCC method allows for a reliable calculation of size‐extensivity effects in the MR case. It has been successfully applied in a number of notoriously difficult quantum chemical problems, such as determination of the automerization barrier in CBD, investigation of valence bond isomers, singlet–triplet energy gap calculations, and most recently in the study of the polyradical character of graphene nanoribbons . The experience with these multireference methods will be used herein to study the remarkably high polyradical character of non‐Kekulé acenes and to provide a theoretically well‐founded picture of the evolution of different spin states for DMBCDs with increasing chain length.…”
Section: Introductionmentioning
confidence: 99%
“…It, furthermore, showed that the computational description of this state was significantly improved when moving from the 6-31G** basis set to a more sophisticated atomic natural orbital basis set even though both basis sets have the same computational cost in the CASSCF and CASPT2 steps. The ionization potentials and characters of the ionized states of various acenes have been studied by MR-AQCC and MR-CI computations 954.…”
mentioning
confidence: 99%